2019
DOI: 10.1111/jphp.13085
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of tuberoinfundibular peptide of 39 on glucocorticoid receptor mediated glutamate/GABA imbalance and cerebral abnormalities against cognitive deficit model

Abstract: Objectives This study is designed to evaluate the role of tuberoinfundibular peptide of 39 (TIP39) in connection with glucocorticoid receptor‐mediated glutamate/GABA abnormalities in chronic unpredictable mild stress (CUMS) model. Methods Male Sprague–Dawley rats were treated with TIP39 (1 and 10 nmol, i.c.v) and diazepam 2 mg/kg throughout the stress period (28 days) in alternate days. Then, rats were subjected for different behavioural activity followed by biochemical, gene expression and histological examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…( Sperman= -0.42, p < 0.05) This is in general accordance with previous research ndings that imply a relationship between high PTH levels and the central nervous system, especially cognition [19,27,28]. The expression of PTH2 receptor (PTH2R) has been found in the cerebral arteries of the central nervous system [29,30], Studies reported that the interaction of the ligand of the PTH2R named as tuberoinfundibular peptide of 39 residues(TIP39) with PTH2R in the brain have in uenced cognition [31][32][33].…”
Section: Discussionsupporting
confidence: 88%
“…( Sperman= -0.42, p < 0.05) This is in general accordance with previous research ndings that imply a relationship between high PTH levels and the central nervous system, especially cognition [19,27,28]. The expression of PTH2 receptor (PTH2R) has been found in the cerebral arteries of the central nervous system [29,30], Studies reported that the interaction of the ligand of the PTH2R named as tuberoinfundibular peptide of 39 residues(TIP39) with PTH2R in the brain have in uenced cognition [31][32][33].…”
Section: Discussionsupporting
confidence: 88%
“…25 The CUMS-induced elevated CORT can alter the metabolism of neuroglial cells that could affect the sequence of glutamate/GABA discharge regulated by glutamic acid decarboxylase enzyme in which converts glutamate to GABA in neuronal and glial cells, however it elevates the brain glutamate and reduces the GABA level in depression. 26 Chronic administration of AKBA improves the altered glutamate/GABA level by increasing GAD enzyme activation in neuronal cells of CUMS rats. Such an adaptogenic response produced by AKBA in stressed rats might be due to suppression of hypothalamic glutaminergic neurons.…”
Section: Discussionmentioning
confidence: 98%
“…Animals routing to hidden platform improves the ability to learn the task which is in direction with the hippocampus CA1, CA3 and DG architect and its neuronal actions [ 24 ]. During the seven days trial, retention time was observed and gradual reduction on day-to-day trial was noted, this shows that continuous exposure of identical activity may reduce the retention time thereby accelerating the learning and memory performance, while augmentation of time spent and platform crossing indicates improvement in reference memory [ 25 ]. Administration of AKBA drastically improved the spatial learning and reference memory performance by reducing retention time, increasing time spent and platform crossing to the target zone.…”
Section: Discussionmentioning
confidence: 99%